Collage of music a culminating activity of students of The child's World A Growing Center Level G & H - Plopinio, Rhys Edgar J.
The title Collage of Music is not only a play of words of the College of Music, but also meaning to be what it is - a compilation of different recorded musical materials (both existing and to be composed) with accompanying modules. The materials and modules are designed to reinforce the academic learning of children with special needs (CSN), outside of the classroom setting, while being open to adaptation into other movement activities. The project will be implemented among children with special needs with mental ages of 8-10 years old who are studying at The Child's World, a school for CSN in Sta. Mesa Heights, Quezon City. The project composition, recording, compilation and pilot testing duration is intended to have a span of one semester.